Large Volume Paracentesis in Patients with Liver Cirrhosis Temporarily Diminishes Blood Cell Count - Mahmood Haghighat; Maryam Ataollahi; Mohammad Hadi Imanieh; Naser Honar; Seyed Mohsen Dehghani; Marzieh Soheili; Seyede Maryam Mahdavi Mortazavi (Iranian Journal of Medical Sciences, 2023)
Background: Large-volume paracentesis is the preferred treatment for patients with severe and refractory ascites. Several complications were reported during therapeutical paracentesis. However, there are very few published studies on the change in blood cell count after paracentesis. This study aimed to evaluate any changes in blood cell counts after ascites fluid drainage. Methods: This study was conducted on patients with severe ascites and chronic liver disease who underwent large-volume paracentesis at Namazi Hospital, in Shiraz, Iran, between March 2021 and February 2022. A data gathering form containing the patient’s medical history, cause of cirrhosis, ascites fluid volume, as well as routine tests including primarily sodium, potassium, and basal creatinine, was filled out. Before and after the surgery, the total blood cell count was measured. Before the procedure, adjustment was made in the case of coagulopathy and albumin deficiency. The effect of factors such as the volume of drained fluid, splenomegaly, antibiotics, and steroid use was assessed on the changes in the number of blood cells. Using the JAMOVI 2.3.9 software, a paired t test and multiple regression were applied for statistical analysis (P<0.001). Results: The study included 37 patients. After the paracentesis procedure, the number of blood cells significantly decreased in all groups (P<0.001). The followings are the amounts of each type of blood cells before and after the procedure: Platelet=153837±91862 and 115648±69136, red blood cells=3.53±0.784 and 3.22±0.705, white blood cells=12.3±7.78 and 8.6±5.5. None of the study variables, including drained volume, splenomegaly, antibiotics, and steroid use, were significant predictors of the changes in the blood cell count after paracentesis (P>0.001).Conclusion: The findings of the present study showed that children with tense ascites who had large-volume paracentesis might experience a sharp drop in blood cell count after the procedure, which was a transient physiological condition.